REMAJA PUTRI PEDESAAN DI INDONESIA BERISIKO ANEMIA DUA KALI LEBIH TINGGI - Nadiyah Nadiyah; Laras Sitoayu; Lintang Puwara Dewanti (GIZI INDONESIA, 2022)
Currently, anemia is developing into a serious nutritional problem in Indonesia. Anemia among adolescent girls reached 32 percent. This study aims to analyze the risk factors for anemia among adolescent girls in Indonesia using the 2018 Basic Health Research data. The data were obtained from the National Institute of Health Research and Development, from 26 provinces in Indonesia. This cross-sectional study was conducted from May to October 2021. Inclusion criteria included adolescent girls aged 12-18 years in Indonesia, having a z-score of body mass index for ages between -5 SD to +5 SD, and having complete data analyzed. The data included socio-economic status (region, parents' education, father's occupation, family size), health services (distance and affordability of transportation costs to health facilities), hand washing habits, sanitation, infectious diseases (ARI and diarrhea), adolescent characteristics (menstruation, number of iron tablets consumed, education, nutritional status, and anemia), improper food habits, fruits, and vegetables consumption and physical activity. The results showed that the percentage of anemic adolescent girls was 23.4 percent. The logistic regression test showed that rural area was a significant risk factor for anemia (p=0.032). Adolescent girls who lived in rural areas had a risk of anemia two times higher than adolescent girls in urban areas (OR= 2,06; 95%CI:1,06-3,98). It is necessary to strengthen an integrated program involving various sectors to reduce anemia among adolescent girls in rural areas. ABSTRAK  Saat ini anemia berkembang menjadi masalah gizi serius di Indonesia. Anemia pada remaja putri mencapai angka 32 persen. Penelitian ini bertujuan untuk menganalisis faktor risiko anemia pada remaja putri di Indonesia menggunakan data Riset Kesehatan Dasar 2018. Data diperoleh dari Badan Penelitian dan Pengembangan Kesehatan RI dari 26 Provinsi di Indonesia. Analisis data menggunakan desain studi cross sectional pada bulan Mei hingga Oktober 2021. Kriteria inklusi meliputi remaja berumur  12-18 tahun  di Indonesia, memiliki  z-skor Indeks Massa Tubuh menurut Umur antara -4 SD hingga +5 SD dan memiliki kelengkapan data yang menjadi variabel penelitian. Data yang analisis meliputi sosial ekonomi (wilayah, pendidikan orang tua, pekerjaan ayah, besar keluarga), pelayanan kesehatan (jarak tempuh dan keterjangkauan biaya transportasi ke fasilitas kesehatan), kebiasaan cuci tangan, sanitasi, penyakit infeksi (ISPA dan diare), karakteristik remaja (menstruasi, jumlah TTD yang diminum, pendidikan remaja, status gizi dan anemia),  kebiasaan konsumsi makanan berisiko, konsumsi buah dan sayur serta aktivitas fisik. Hasil studi menunjukkan persentase remaja putri anemia sebesar 23,4 persen. Hasil uji regresi logistik menunjukkan wilayah pedesaan menjadi faktor risiko anemia yang signifikan (p=0,032). Remaja putri yang tinggal di pedesaan memiliki risiko anemia 2 kali lebih tinggi dibandingkan remaja putri di perkotaan (OR= 2,06; 95%CI:1,06-3,98). Perlunya penguatan program penurunan masalah anemia yang terintegrasi dari berbagai sektor di pedesaan. Kata kunci: remaja putri Indonesia, anemia, pedesaan